Identifying demographics of high risk male and LGBTQ+ survivors of domestic abuse from acute London hospital referrals – case review. (January 2023) - Smith, Jo; Baker, Emily; Hepworth, Eleanor; Melendez-Torres, GJ; Nicholas, Rachel; Cohen, Charlotte E
Background: Heterosexual men, and lesbians, gay men, bisexual, transgender and queer (LGBTQ+) people are under-described in research and resources relating to domestic abuse (DA), compared to heterosexual cisgender female survivors. Many of the identified DA cases within our hospital organisation that warrant onward multidisciplinary referral, due to ongoing high harm risk, are for male and LGBTQ+ survivors. We aimed to describe demographics and risk patterns of these cases, to inform and equip our specialist Independent Domestic Violence Advocacy (IDVA) service. Method: We performed a retrospective case-note review of all Multi-Agency Risk Assessment Conferences (MARAC) referrals for DA, featuring male & LGBTQ+ subjects, across Chelsea and Westminster Hospital NHS Foundation Trust (CWFT), London, UK between April 2019 - December 2020. We recorded demographic data of referral subjects and perpetrators; the origin of referral; the nature of the initial presenting complaint and whether the DA was identified by the subject or by the healthcare provider on enquiry; and recorded rates of co-marginalising and harm risk factors (dependent children, disability, mental health comorbidity, HIV status, drug use, homelessness). Results: We identified 33 cases: 10.2% of CWFT's total MARAC referrals were for men, and 6.7% for LGBTQ+ people (cf. national figures from the same period: 0.1% and 1.3% respectively). Nearly half (48.5%, 16) of the referrals came from sexual health services, just under half (45.5%, 15) from Emergency Departments. 42% (14) disclosures were elicited incidentally during routine enquiry. Six (18%) subjects were also known survivors of sexual violence in addition to DA. The majority (79%, 26) of perpetrators were current or ex-intimate partners. Eight (24%) of the subjects had children under 18. High rates of co-marginalisation factors were present, including use of recreational drugs (45.5%, 15), belonging to an ethnic minority (39.4%, 13), living with HIV (24.2%, 8), living with a disability (18%, 6), mental health comorbidity (27.3%, 9), and experience or risk of homelessness (9%, 3). Conclusions: Our trust reports a high rate of male and LGBTQ+ high-risk DA referrals, and amongst these there is a high rate of intersecting disadvantages and risk factors. This underlines a need for inclusivity for marginalised groups, inbuilt into domestic abuse health responses. The high rate of disclosure during routine enquiry for domestic abuse supports the use of DA routine enquiry in sexual health settings, and points towards the utility of selective enquiry in other settings (for example, heterosexual males presenting with injuries to emergency departments). We hope that by working with a specialised LGBTQ+ IDVA, we will improve both prompt identification and better outcomes for more GSM patients.